Comparative tolerability of treatments for acute migraine: A network meta-analysis. (September 2017) - Thorlund, Kristian; Toor, Kabirraaj; Wu, Ping; Chan, Keith; Druyts, Eric; Ramos, Elodie; Bhambri, Rahul; Donnet, Anne; Stark, Richard; Goadsby, Peter J
Introduction: Migraine headache is a neurological disorder whose attacks are associated with nausea, vomiting, photophobia and phonophobia. Treatments for migraine aim to either prevent attacks before they have started or relieve attacks (abort) after onset of symptoms and range from complementary therapies to pharmacological interventions. A number of treatment-related adverse events such as somnolence, fatigue, and chest discomfort have previously been reported in association with triptans. The comparative tolerability of available agents for the abortive treatment of migraine attacks has not yet been systematically reviewed and quantified. Methods: We performed a systematic literature review and Bayesian network meta-analysis for comparative tolerability of treatments for migraine. The literature search targeted all randomized controlled trials evaluating oral abortive treatments for acute migraine over a range of available doses in adults. The primary outcomes of interest were any adverse event, treatment-related adverse events, and serious adverse events. Secondary outcomes were fatigue, dizziness, chest discomfort, somnolence, nausea, and vomiting. Results: Our search yielded 141 trials covering 15 distinct treatments. Of the triptans, sumatriptan, eletriptan, rizatriptan, zolmitriptan, and the combination treatment of sumatriptan and naproxen were associated with a statistically significant increase in odds of any adverse event or a treatment-related adverse event occurring compared with placebo. Of the non-triptans, only acetaminophen was associated with a statistically significant increase in odds of an adverse event occurring when compared with placebo. Overall, triptans were not associated with increased odds of serious adverse events occurring and the same was the case for non-triptans. For the secondary outcomes, with the exception of vomiting, all triptans except for almotriptan and frovatriptan were significantly associated with increased risk for all outcomes. Almotriptan was significantly associated with an increased risk of vomiting, whereas all other triptans yielded non-significant lower odds compared with placebo. Generally, the non-triptans were not associated with decreased tolerability for the secondary outcomes. Discussion: In summary, triptans were associated with higher odds of any adverse event or a treatment-related adverse event occurring when compared to placebo and non-triptans. Non-significant results for non-triptans indicate that these treatments are comparable with one another and placebo regarding tolerability outcomes.